Chemical constituents and antioxidant activities of Aquilaria malaccensis Lamk. (agarwood) leaves - Nik Noor Asma, Nik Wil (2019)
Aquilaria species contains variety of secondary metabolites including various phenolic compounds which have been reported as excellent antioxidants. A study on phytochemical and antioxidant properties of Aquilaria malaccensis from Thymelaeaceae family was performed. The extraction of phytochemicals from the leaves were performed using conventional extraction methods: reflux extraction using water and maceration using methanol to obtain water extract (WE) and methanol extract (ME), respectively. Solvent–solvent extraction, fractionation and separation using different chromatographic techniques (column chromatography and thin layer chromatography) were used for isolation of pure compounds. In order to identify the volatile aroma compounds in the leaves of A. malaccensis, two methods were used namely solid-phase microextraction (SPME) and direct thermal desorption (DTD), in combination with gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) analysis. The ultra-highperformance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QToF/MS) was used for determination of non-volatile chemical compounds present in the leaves. The potential antioxidative activity of the leaves extracts of A. malaccensis was evaluated via radical scavenging assay (DPPH) and copper reducing antioxidant capacity (CUPRAC) assays. Significant differences were based on p values where p<0.05 were considered significantly different and vice-versa. Some of the commonly identified chemical components were n-hexadecanoic acid, eudesmol and oxo-agarospirol. WE and ME extracts with the highest total phenolic contents (191.005 ± 0.002 and 177.927 ± 0.001 mg of GAEs/g extract) showed strong reducing power and scavenging radical activity. Friedelanol and friedelin were isolated from the fractionation of hexane and dichloromethane extracts, respectively. The structure of the isolated compounds was elucidated by using spectroscopic methods namely 1D (1H, 13C, DEPTQ), 2D (COSY, HSQC, HMBC) NMR, MS, UV, FTIR and by comparison with literature values of published data spectra.